2012
DOI: 10.1002/hep.25658
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of Japanese patients with type 1 autoimmune hepatitis

Abstract: The long-term outcome of patients with autoimmune hepatitis (AIH) in Japan has not been well-defined. The aim of this study was to clarify the outcome of this disease over a long follow-up period compared with that of the general Japanese population as well as that among patients. A total of 203 AIH patients were enrolled for a mean follow-up period of 131 months. All patients were treated with corticosteroids with or without azathioprine. The overall survival of AIH patients was similar to that of the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 36 publications
10
102
1
1
Order By: Relevance
“…Another study showed that cirrhosis at presentation is associated with poorer prognoses (16). In contrast, other studies have reported similar outcomes in patients with and without cirrhosis at presentation (17,18). In the present study, the cumulative survival rate was also significantly lower in the cirrhosis cases.…”
Section: Discussioncontrasting
confidence: 51%
“…Another study showed that cirrhosis at presentation is associated with poorer prognoses (16). In contrast, other studies have reported similar outcomes in patients with and without cirrhosis at presentation (17,18). In the present study, the cumulative survival rate was also significantly lower in the cirrhosis cases.…”
Section: Discussioncontrasting
confidence: 51%
“…One major problem of AIH is that an acute presentation or exacerbation of the disease can progress to liver failure (4,5). Furthermore, patients with AIH can be susceptible to hepatocellular carcinoma (6); therefore, patients should be followed-up for exacerbation and hepatocellular carcinoma (7). Primary biliary cirrhosis (PBC) is characterized by nonsuppurative cholangitis and autoimmune-mediated destruction of the small or medium-sized bile ducts (8).…”
Section: Introductionmentioning
confidence: 99%
“…There are ethnic and racial disparities in these serological changes. For example, the prevalence of anti-SMApositive AIH ranges from 19% to 45% in Asia-Pacific area, 22 45-84% in Americans, and even higher in Australians (around 90%) 23 . It should be noted that autoantibody profile alone does not verify the diagnosis of AIH, since autoantibodies can also be positive in various immune disorders and other liver diseases.…”
Section: Clinical Featuresmentioning
confidence: 99%